Catecholaminergic dysfunction drives postural and locomotor deficits in a mouse model of spinal muscular atrophy - John G. Pagiazitis; Nicolas Delestrée; Leonie Sowoidnich; Nandhini Sivakumar; Christian M. Simon; Athanasios Chatzisotiriou; Maria Albani; George Z. Mentis (Cell Reports)
Summary: Development and maintenance of posture is essential behavior for overground mammalian locomotion. Dopamine and noradrenaline strongly influence locomotion, and their dysregulation initiates the development of motor impairments linked to neurodegenerative disease. However, the precise cellular and circuit mechanisms are not well defined. Here, we investigated the role of catecholaminergic neuromodulation in a mouse model of spinal muscular atrophy (SMA). SMA is characterized by severe motor dysfunction and postural deficits. We identify progressive loss of catecholaminergic synapses from spinal neurons that occur via non-cell autonomous mechanisms. Importantly, the selective restoration of survival motor neuron (SMN) in either catecholaminergic or serotonergic neurons is sufficient to correct impairments in locomotion. However, only combined SMN restoration in both catecholaminergic and serotonergic neurons or pharmacological treatment with l-dopa improve the severe postural deficits. These findings uncover the synaptic and cellular mechanisms responsible for the postural and motor symptoms in SMA and identify catecholaminergic neuromodulation as a potential therapeutic target.